The colonial kangaroo hunt - Gelder, Ken, 1955-; Weaver, Rachael (Miegunyah Press series ;, 2020)
From the arrival of Captain James Cook in 1770 to classic children's tale Dot and the Kangaroo, Ken Gelder and Rachael Weaver examine hunting narratives in novels, visual art and memoirs to discover how the kangaroo became a favourite quarry, a relished food source, an object of scientific fascination, and a source of violent conflict between settlers and Aboriginal people. The kangaroo hunt worked as a rite of passage and an expression of settler domination over native species and land. But it also enabled settlers to begin to comprehend the complexity of bush ecology, raising early concerns about species extinction and the need for conservation and the preservation of habitat.